MODERN APPROACHES TO DEVELOPING STUDENTS’ COMMUNICATIVE SPEECH IN THE SUBJECT OF ‘NATIVE LANGUAGE’ IN PRIMARY SCHOOL - Bekberganova Nazokat Oybek qizi (Bright Mind Publishing, 2025)
This article analyzes modern approaches to developing students’ communicative speech through the subject “Native language” in primary school. In today’s context of globalization, the educational process emphasizes not only the acquisition of theoretical knowledge but also the cultivation of students’ communication culture. Therefore, the article scientifically examines the concept of communicative competence, its components, and the methodological foundations for achieving it at the primary education stage. In particular, the effectiveness of interactive methods, information and communication technologies, play-based activities, and tasks based on oral folklore is highlighted. The study explores approaches that contribute to the development of students’ oral and written speech skills, independent thinking, and the ability to express their ideas clearly. As a result, the article provides scientific and methodological recommendations of both theoretical and practical significance for primary school teachers.
Keywords: Communicative competence, speech development, mother tongue education, primary education methodology, interactive methods, information and communication technologies, oral speech, written speech, independent thinking, communication culture.